A Case Study of Floating Offshore Super-Long Steel Pipeline Combing with Field Monitoring - Jin Yu (MDPI AG, 2021)
How to control deformation and avoid resonance is the key to ensuring the safety of the super-long pipeline when it is floating in the sea. Based on the deformation warning value of pipeline prototype composite material obtained from laboratory tests, the raw water pipeline project in Tong’an Xiamen adopts wireless communication equipment to transmit data, supplemented by aerial photography technology to monitor and feedback the strain and vibration during the dynamic construction of long-distance pipeline floating transportation. Combined with dynamic construction, this monitoring method avoids excessive deformation and resonance of the steel pipeline during floating transportation, and prevents the destruction of the anticorrosive coating. The airtightness test after completion shows that the whole pipeline meets the acceptance requirements. The monitoring results show that the strain at the bent position of the pipeline is large in the process of floating transportation, and the jacking speed and position of the tugboats have an important influence on the deformation of the pipeline. The same type of project should focus on these aspects and timely feedback monitoring data. At the same time, the study also provides detailed strain, modal analysis and effective monitoring technology for the safety of offshore steel pipeline floating transportation.